2015
DOI: 10.5799/ahinjs.02.2015.01.0171
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo hemorrhagic fever and pregnancy: Two cases

Abstract: Crimean-Congo Hemorrhagic Fever (CCHF) is a viral zoonosis, transmitted to humans by either: the Hyalomma species of ticks; or by direct contact with body fluids or tissues of infected humans or domestic animals. CCHF can result in death through clinical progression of hemorrhagic fever (1). Tokat Province in Turkey is where CCHF cases are seen at the highest rate.In this article, the cases of two pregnant women are discussed. The women applied in Tokat with a fever and were diagnosed with CCHF. Along with sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Up to now, overall 15 pregnant CCHF cases have been reported in the literature from Turkey including our cases [7][8][9][10][11] . Only one mother died due to intracerebral hemorrhage.…”
Section: Review Of the Literaturementioning
confidence: 81%
See 3 more Smart Citations
“…Up to now, overall 15 pregnant CCHF cases have been reported in the literature from Turkey including our cases [7][8][9][10][11] . Only one mother died due to intracerebral hemorrhage.…”
Section: Review Of the Literaturementioning
confidence: 81%
“…Maternal and fetal/ neonatal mortality rates were found to be 6.6% (1/15) and 40% (6/15), respectively in Turkish cases (Table 1). Fetal mortality was Ergonul et al [7] 38 Dizbay et al [8] 36 Survival Survival -+ Present 36 th week Aydemir et al [11] 30 Survival Survival N -No 37 th week Duygu et al [10] 17 found in 3/4 in the first trimester, 4/8 in the first 20 weeks, and 2/7 in the second 20 weeks. Unlike what Pschenichnaya et al [12] reported, fetal mortality was found to be different in terms of pregnancy period in our study.…”
Section: Review Of the Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…In a case report of a patient infected with CCHF in week 30 of pregnancy, the baby was born at 37 weeks completely healthy with no signs or symptoms related to the disease [75] . In another report, two pregnant patients in Turkey survived and gave birth to healthy babies by vaginal delivery [76] . A review of pregnant patients reported that maternal mortality was 34% (14/41) and fetal/neonatal mortality was 58.5% (24/41), and the presence of hemorrhage was associated with maternal and fetal mortality [77] .…”
Section: Prognostic Factors Fatality and Discharge Criteriamentioning
confidence: 99%